2019
DOI: 10.1186/s12987-019-0123-z
|View full text |Cite
|
Sign up to set email alerts
|

Claudin-5: gatekeeper of neurological function

Abstract: Tight junction proteins of the blood–brain barrier are vital for maintaining integrity of endothelial cells lining brain blood vessels. The presence of these protein complexes in the space between endothelial cells creates a dynamic, highly regulated and restrictive microenvironment that is vital for neural homeostasis. By limiting paracellular diffusion of material between blood and brain, tight junction proteins provide a protective barrier preventing the passage of unwanted and potentially damaging material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
277
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 342 publications
(309 citation statements)
references
References 148 publications
12
277
0
1
Order By: Relevance
“…Only a handful of studies have explored molecular and epigenetic regulation of cldn5 despite its role in several inflammatory conditions and neurological disorders, including stroke (25), glioblastoma (26), multiple sclerosis, and Alzheimer's disease (27). In an elegant set of papers, Taddei et al showed that VE-cadherin mediates up-regulation of cldn5 and epigenetic regulation of endothelial gene expression (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…Only a handful of studies have explored molecular and epigenetic regulation of cldn5 despite its role in several inflammatory conditions and neurological disorders, including stroke (25), glioblastoma (26), multiple sclerosis, and Alzheimer's disease (27). In an elegant set of papers, Taddei et al showed that VE-cadherin mediates up-regulation of cldn5 and epigenetic regulation of endothelial gene expression (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, during adolescence and young adulthood roughly 25% of 22qDS patients develop SZ, a 25-fold increase in risk over the general population (Arinami, 2006;Karayiorgou & Gogos, 2004; Van, Boot, & Bassett, 2017). The 22q11.2 deletion includes junctional and mitochondrial genes that could influence barrier function (Arinami, 2006;Devaraju & Zakharenko, 2017;Greene et al, 2018;Greene, Hanley, & Campbell, 2019). However, the status of the blood brain barrier (BBB), the highly specialized central nervous system (CNS) endothelial cells, in 22qDS is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…A violation of BBB integrity disrupts Aβ transport contributing to the excessive accumulation of toxic Aβ in the brain and further aggravating pathology [60]. Matrix metalloprotein-9 (MMP-9) and tight junction protein Claudin-5 have been shown to regulate BBB permeability and play an important role in neuropathologies such as Alzheimer's disease [61,62]. In the rat Alzheimer's disease model, resveratrol defends BBB integrity by reducing advanced glycation end products (RAGE), matrix metalloprotein-9 (MMP-9) and increasing Claudin-5 but also reduces neuroinflammation by affecting nuclear factor NF-κB expression [63].…”
Section: Central Nervous System Inflammation and Integrity Disordersmentioning
confidence: 99%